2011
DOI: 10.1073/pnas.1105414108
|View full text |Cite
|
Sign up to set email alerts
|

Different telomere-length dynamics at the inner cell mass versus established embryonic stem (ES) cells

Abstract: Murine embryonic stem (ES) cells have unusually long telomeres, much longer than those in embryonic tissues. Here we address whether hyper-long telomeres are a natural property of pluripotent stem cells, such as those present at the blastocyst inner cell mass (ICM), or whether it is a characteristic acquired by the in vitro expansion of ES cells. We find that ICM cells undergo telomere elongation during the in vitro derivation of ES-cell lines. In vivo analysis shows that the hyper-long telomeres of morula-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 52 publications
4
72
0
Order By: Relevance
“…Telomerase activity is high at the blastocyst stage during which telomere length is determined for a given individual. 6,7 Thereafter telomeres progressively shorten throughout life due to the down-regulation of telomerase and the loss of telomeric sequences associated with the replication of DNA ends with every cell division. Consequently, cells reaching a critical short telomere length enter into cellular senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Telomerase activity is high at the blastocyst stage during which telomere length is determined for a given individual. 6,7 Thereafter telomeres progressively shorten throughout life due to the down-regulation of telomerase and the loss of telomeric sequences associated with the replication of DNA ends with every cell division. Consequently, cells reaching a critical short telomere length enter into cellular senescence.…”
Section: Introductionmentioning
confidence: 99%
“…High telomerase activity is an important characteristic of ESCs. Our current knowledge of telomere maintenance in ESCs is largely derived from studies in mouse ESCs (mESCs): telomere elongation has been observed during in vitro derivation of mESCs (Varela et al, 2011); loss of telomerase activity in mESCs resulted in progressive telomere loss, genomic instability, aneuploidy and telomere fusion, eventually leading to reduced growth rates (Niida et al, 1998); telomerase overexpression enhanced self-renewal, improved resistance to apoptosis and increased proliferation in mESCs (Armstrong et al, 2005). Tetraploid embryo complementation experiments have shown that telomerase-deficient mESCs with short telomeres lose their ability to generate complete ESC-pups (Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there have been no reports of generating embryos from a combination of mES and trophoblast stem cells [84]. The failure of aggregated stem cell lines derived thus far to spontaneously form embryos is likely to reflect the fact that stem cell lines have a range of properties [85][86][87] that are not identical either to zygotes [88,89] or to cells that have been freshly isolated from embryos [43][44][45][46][47]. While these negative findings do not strictly rule out the possibility that later-stage blastomeres or pluripotent stem cells ''could'' combine in some way to generate an embryo (it is logically impossible to prove something from a negative finding), they strongly suggest that collective reconstitution of an embryo from cells of a reaggregated morula-stage embryo (Fig.…”
Section: Collectively Generating a Developmental Sequence Is Not Totimentioning
confidence: 99%
“…However, there is no scientific evidence to date that twinning at the blastocyst stage involves totipotent cells, and multiple studies have concluded exactly the opposite; that is, that blastocyst cells are quite unlike totipotent zygotes on multiple parameters [43][44][45][46][47][85][86][87] and that blastocyst cells are completely incapable of producing a whole embryo when isolated from each other [145][146][147], instead producing only stem cell lines. These observations argue strongly that twinning does not involve totipotent cells, but rather relies on some other developmental mechanism.…”
Section: Twinningmentioning
confidence: 99%
See 1 more Smart Citation